SQL-Based Fuzzy Query Mechanism Over Encrypted Database - Liu, Zheli; Li, Jingwei; Li, Jin; Jia, Chunfu; Yang, Jun; Yuan, Ke (International journal of data warehousing and mining, 2014)
With the development of cloud computing and big data, data privacy protection has become an urgent problem to solve. Data encryption is the most effective way to protect privacy; however, it will change the data format and result in: 1. database structure and application software will be changed; 2. structured query language (SQL) operations cannot work properly, especially in SQL-based fuzzy query. As a result, it is necessary to provide an SQL-based fuzzy query mechanism over encrypted databases, including traditional databases and cloud outsourced databases. This paper establishes a secure database system using format-preserving encryption (FPE) as the underlying primitive to protect the data privacy while not change the database structure. It further proposes a new SQL-based fuzzy query mechanism supporting directly query over encrypted data, which is constructed by FPE and universal hash function (UHF). The security of the proposed mechanism is analyzed as well. In the end, it makes extensive experiments on the system to demonstrate its practical performance.